A multinuclear NMR perspective on the complexation between bisboronic acids and bisbenzoxaboroles with cis-diols. (26th January 2018) - Larcher, Adèle; Lebrun, Aurélien; Smietana, Michael; Laurencin, Danielle
Abstract : A new way of using solution NMR (especially 19 F NMR) to study organoboron molecule/ cis -diol equilibria is presented. Abstract : The interaction between boronic acids and cis -diols is an intense area of research, with numerous applications in sensing, separation, drug delivery, and materials science. Several analytical tools have been proposed over the past 20 years to probe these interactions, but most of them are limited by shortcomings such as high concentration requirements and/or the lack of clear evidence of the nature of the species present in solution. These drawbacks are all the more problematic in the case of compounds bearing multiple binding sites. In this work, a multinuclear ( 1 H, 11 B, 19 F) NMR spectroscopy approach has been used to investigate for the first time the equilibria between bisboronic acids and bisbenzoxaboroles (as well as their monofunctional counterparts) with representative cis -diols, including catechol derivatives. The developed method is shown to provide valuable and straightforward insight into the nature of the species in solution, and the way in which the equilibria can be affected by the complexation media. In particular, the interest of using a 19 F-tag on the cis -diol is emphasized.